2013
DOI: 10.1128/mcb.01716-12
|View full text |Cite
|
Sign up to set email alerts
|

IDOL Stimulates Clathrin-Independent Endocytosis and Multivesicular Body-Mediated Lysosomal Degradation of the Low-Density Lipoprotein Receptor

Abstract: The low-density lipoprotein receptor (LDLR) is a critical determinant of plasma cholesterol levels that internalizes lipoprotein cargo via clathrin-mediated endocytosis. Here, we show that the E3 ubiquitin ligase IDOL stimulates a previously unrecognized, clathrin-independent pathway for LDLR internalization. Real-time single-particle tracking and electron microscopy reveal that IDOL is recruited to the plasma membrane by LDLR, promotes LDLR internalization in the absence of clathrin or caveolae, and facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 71 publications
3
66
0
1
Order By: Relevance
“…Unfortunately, IDOL protein levels could not be measured because of the nonspecifi city of the available commercial antibodies ( 41 ). However, IDOL mRNA levels did not differ in PCSK9 KO tissues (supplementary Fig.…”
Section: Synergistic Effect Of Ovariectomy and Pcsk9 Defi Ciency On Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, IDOL protein levels could not be measured because of the nonspecifi city of the available commercial antibodies ( 41 ). However, IDOL mRNA levels did not differ in PCSK9 KO tissues (supplementary Fig.…”
Section: Synergistic Effect Of Ovariectomy and Pcsk9 Defi Ciency On Pmentioning
confidence: 99%
“…Aside from PCSK9, another "degrader" of the LDLR is the inducible degrader of LDLR (IDOL), an E3 ubiquitin ligase that ubiquitinates the cytosolic tail of the LDLR, VLDLR, or apoER2 ( 39 ), leading to their subsequent degradation by lysosomes ( 40,41 ), and that is known to be induced by liver X receptor activation in response to elevated levels of cellular cholesterol. Unfortunately, IDOL protein levels could not be measured because of the nonspecifi city of the available commercial antibodies ( 41 ).…”
Section: Synergistic Effect Of Ovariectomy and Pcsk9 Defi Ciency On Pmentioning
confidence: 99%
“…From this analysis the 4 proteins APOE, MYOC, ELANE (UniProt ID: P08246) and KNG1 (UniProt ID: P01042) in this cluster are found to be involved in heparin binding. [21][22][23][24] Further, based on the localization of the proteins [25][26][27][28][29][30][31] in Cluster 2 ( Figure 3) it is most probable that STAT3 (UniProt ID: P40763) interacts with POAG proteins APOE and CYP1B1 in the cytoplasm. Also MYOC might interact with POAG proteins FN1 and CYP1B1 in the endoplasmic reticulum.…”
Section: Validation Of the Toolmentioning
confidence: 99%
“…Although IDOL can interact with LDLR at multiple steps in its cellular itinerary, plasma membrane-localized LDLR is particularly sensitive to IDOL-mediated ubiquitylation (16). Once ubiquitylated, LDLR is rapidly removed from the plasma membrane and sorted by the ESCRT (endosomal sorting complexes required for transport) machinery toward the lysosome for degradation (16,17). The clinical relevance of IDOL in humans is highlighted by recent studies that found an association between common and * This work was supported in part by Landsteiner Foundation for Blood Trans- rare genetic variance in the IDOL locus and circulating levels of LDL cholesterol.…”
mentioning
confidence: 99%
“…Although IDOL can interact with LDLR at multiple steps in its cellular itinerary, plasma membrane-localized LDLR is particularly sensitive to IDOL-mediated ubiquitylation (16). Once ubiquitylated, LDLR is rapidly removed from the plasma membrane and sorted by the ESCRT (endosomal sorting complexes required for transport) machinery toward the lysosome for degradation (16,17 …”
mentioning
confidence: 99%